c. h = -4
2006-12-26 12:20:39
·
answer #1
·
answered by kim 2
·
3⤊
0⤋
- 9h - 6+ 12h + 40 =22combine like terms
3h+34=22 subtract 34 from each side
3h=-12 divide by 3
h=-4
c. h = -4
is correct
2006-12-26 14:01:41
·
answer #2
·
answered by mu_do_in 3
·
1⤊
0⤋
-9h - 6 + 12h + 40 = 22
-6 + 3h + 40 = 22
3h + 40 = 28
3h = -12
h = -4
2006-12-26 12:00:38
·
answer #3
·
answered by JC 7
·
1⤊
0⤋
- 9h - 6+ 12h + 40 =22
3h + 34 = 22
3h = 22 - 34
3h = -12
h = -12 : 3
h = -4
Solution is c) -4.
<>><
2006-12-26 15:07:21
·
answer #4
·
answered by aeiou 7
·
0⤊
0⤋
First: combine "like" terms > combine "h variables:
-9h + 12h - 6 + 40 = 22
3h + 34 = 22
Second: subtract 34 from both sides > opposite side means opposite sign
3h + 34 - 34 = 22 - 34
3h = -12
Third: solve for "h" by keeping it on one side > divide both sides by 3
3h/3 = -12/3
h = -4
2006-12-26 12:22:06
·
answer #5
·
answered by ♪♥Annie♥♪ 6
·
1⤊
0⤋
the answer is -4.
-9h-6+12h++40=22
add -9h +12h
-6+3h+40=22
add -6+40
3h+34=22
now minus -34 from 22
3h = -12
h = -4
2006-12-26 12:01:39
·
answer #6
·
answered by wookie 2
·
0⤊
0⤋
-9h + 12h -6 + 40 = 22
3h + 34 = 22
3h = -12
h = -4
# c is right!
2006-12-26 12:00:41
·
answer #7
·
answered by Chocogal 7
·
1⤊
0⤋
Combine h's together to simplify.
-9h-6+12h+40=22
3h-6+40=22
Simplfy as much as possible
3h+34=22
Solve
3h+34-34=22-34
3h=-12
h=-4
The answer is c.
2006-12-26 13:33:22
·
answer #8
·
answered by lulu 3
·
0⤊
0⤋
-9h - 6 + 12h + 40 = 22
3h + 34 = 22 (Subtract 34 from both sides)
3h = -12 (Divide both sides by 3)
h = -4
The correct answer is c, h = -4
QED
2006-12-27 09:31:43
·
answer #9
·
answered by CSUFGrad2006 5
·
0⤊
0⤋
- 9h - 6+ 12h + 40 =22
3h - 6 + 40 = 22
3h - 34 = 22
+ 34 +34
------ ------
3h = 56
---- -----
3 3
h = 9 2/56 = 9 1/28
2006-12-26 14:41:49
·
answer #10
·
answered by sk8er V 2
·
0⤊
0⤋
3h+34=22
3h=-12
h=-4
option C
2006-12-26 11:58:52
·
answer #11
·
answered by raj 7
·
1⤊
0⤋